The Press and Race : Mississippi Journalists Confront the Movement - Davies, David R. (David Randall), 1957- (Book collections on Project MUSE., 2001)
For southern newspapers and southern readers, the social upheaval in the years following Brown v. Board of Education (1954) was, as Time put it in 1956, "the region's biggest running story since slavery." The southern press struggled with the region's accommodation of the school desegregation ruling and with black America's demand for civil rights. The nine essays in The Press and Race illuminate the broad array of print journalists' responses to the civil rights movement in Mississippi, a state that was one of the nation's major civil rights battlegrounds. Three of the journalists covered won.